Application of the Organizational Modernization Model (MMGO) at Cooperativa Lechera Colactabio - Vargas Guzmán, Wilson Camilo; Araujo Trujillo, Claudia Patricia; Obregoso Gonzalez, Yeison Leonardo (Cooperativismo & Desarrollo, 2022)
This research article consolidates the results obtained in the initial diagnosis made to Colactabio, a solidarity economy enterprise for the production and marketing of raw milk. Through the application of the Modernization Model for Organizational Management (MMGO) developed by the EAN University, and based on the results obtained, to increase its level of competitiveness through the updating of organizational strategies, achieving the guidelines for the directives, establishing the strategic route to follow, and thus optimize the production, transportation, quality, commercialization processes and their impact outside the municipality. The participatory action research methodology was used with the collaboration of the organization's manager. It was found that the cooperative, established more than 15 years ago still develops its processes informally, with processes focused on the product and without competitive projection outside its market environment, corresponding to stage 2 at general level. The components with the highest performance were Associativity, confirming the fulfillment of its constitutive objective of improving the living conditions of its members, followed by Marketing Management with a good part of its production sold to companies producing dairy products in surrounding areas to the locality. On the contrary, the components that presented the lowest development percentages were Imports and exports, located in stage 1 as a result of the lack of projection of growth in competitive coverage. We can conclude that despite the adverse conditions that threaten this important primary production sector, the modernization of entities such as Colactabio is viable and promote an increase in their competitive level towards regional, national and even international markets.
Keywords: organizations Managemen; cooperatives; associativiness; production; commercialization